ELECTROCHEMICAL INVESTIGATION OF THE INHIBITING EFFECT EXERTED BY THE SULFURIC ACID DIAMIDE ON BRONZE CORROSION - CHELARU, Julieta Daniela; GAVRILOAE, Maria; MUREŞAN, Liana Maria (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The present study is aiming to study the effect of sulfuric acid diamide (SAD) on corrosion of bronze CuSn8. In order to determine the optimal corrosion inhibiting effect, SAD was tested at different concentrations. The inhibiting effect of the SAD was investigated by electrochemical methods, in a 0.2 g / L Na2SO4 + 0.2 g / L NaHCO3 (pH = 5) solution simulating acid rain. The results show that SAD exerts a good protection in case of CuSn8.